2013
DOI: 10.1558/cj.v21i1.131-144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multimedia Vocabulary Annotations and Learning Styles on Vocabulary Learning

Abstract: This first goal of the study described here was to investigate the effectiveness of three types of vocabulary annotations on vocabulary learning for EFL college students in Taiwan: text annotation only, text plus picture, and text plus picture and sound. The second goal of the study was to determine whether learners with certain perceptual learning styles benefited more from a particular type of vocabulary annotations. The perceptual learning styles investigated were auditory, visual-verbal (with text), visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
79
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 10 publications
14
79
3
1
Order By: Relevance
“…Also, 21 % students agreed and 29 % students slightly disagreed. Their responses seem to support previous studies that comparing to text-only, picture-only, or text plus picture, video which is the combination of text, picture and audio was the most effective type of "annotation" to facilitate vocabulary learning (Al-Seghaver, 2001;Yeh & Wang, 2003 ). The possible explanation is that the picture provides learners visual input so that they can imagine the "context" while the audio input helps to deepen the image by saying the words and lines out.…”
Section: The Level Of Vocabulary In Tv Drama Is Appropriate For Mesupporting
confidence: 84%
“…Also, 21 % students agreed and 29 % students slightly disagreed. Their responses seem to support previous studies that comparing to text-only, picture-only, or text plus picture, video which is the combination of text, picture and audio was the most effective type of "annotation" to facilitate vocabulary learning (Al-Seghaver, 2001;Yeh & Wang, 2003 ). The possible explanation is that the picture provides learners visual input so that they can imagine the "context" while the audio input helps to deepen the image by saying the words and lines out.…”
Section: The Level Of Vocabulary In Tv Drama Is Appropriate For Mesupporting
confidence: 84%
“…He discovered that the subjects who used annotations on two or more occasions performed significantly better on the vocabulary test, but no significant difference was found in the text comprehension. Another study that includes sound annotation in the investigation is a study by Yeh and Wang (2003). EFL students in Taiwan were divided into three groups with three types of annotations: textual definition; textual definitions and pictures; and textual definitions, pictures, and sounds.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Many studies have examined and reported the positive effects of visual glosses (e.g., pictures or images) in second language (L2) vocabulary acquisition in multimodal environments (Chun & Plass, 1996;Lomicka, 1998;Al-Seghayer, 2001;Yoshii & Fraitz, 2002;Yeh & Wang, 2003;Sato & Suzuki, 2010). These results are underpinned by the Dual Coding Theory (Paivio, 1971) for multimedia learning (Mayer & Sim, 1994), which states that presenting information in both verbal and visual modes leads to longer retention of the target information than with only one code.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they tended to focus on the appropriate combination of different glosses; Chun & Plass (1996) claim the combination of verbal and pictorial glosses is more effective in incidental L2 vocabulary learning than only presenting verbal or pictorial gloss. Yeh & Wang (2003) also stressed that the combination of verbal and pictorial glosses can increase target vocabulary retention more than integrating three gloss types: verbal, picture, and sound, and only one gloss type. As information presentation with multimodal functions has been developing, the impact of different visual glosses based on the same image should be examined.…”
Section: Introductionmentioning
confidence: 99%